Bibliometric analysis of research on social entrepreneurship - Nurul Aziza; M. Adhi Prasnowo; Nurmawati Nurmawati (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to identify research trends and patterns in the field of social entrepreneurship.Method — We employed a descriptive bibliometric analysis methodology to identify publications related to social entrepreneurship between 2020 and 2022. Using the Scopus database, we conducted data collection by utilizing the keyword "social entrepreneurship" and imposing a limit of 200 journal articles with the assistance of Publish or Perish (PoP) software for metadata extraction. To carry out the bibliometric analysis, we utilized the VOSviewer software.Result — The findings from bibliometric mapping conducted with VOSviewer indicate that, within the timeframe of 2020-2022 and within Scopus indexed publications focusing on social entrepreneurship research, a total of 200 articles were gathered, all of which provided complete year information. Notably, the most significant surge in publications was observed in 2020, with a total of 155 articles being published in journals (constituting 65% of the total), while the lowest number of publications occurred in 2022, with just 15 publications (making up 7.5% of the total). The bibliometric mapping exercise revealed the emergence of five distinct keyword clusters: entrepreneurial intention, digital entrepreneurship, entrepreneur, social entrepreneurship, and entrepreneurship.Contribution — This study offers a substantial scholarly contribution to forthcoming directions in entrepreneurship literature, specifically within the realm of social entrepreneurship research. The research approach employed here involves bibliometric analysis, which is recommended as an initial step for identifying areas where future research can make meaningful contributions and uncover sustainable research avenues.